Combined first-trimester Down syndrome screening in HIV-infected women. (August 2016) - Chougrani, Imène; Muller, Françoise; Marcelin, Louis; Tsatsaris, Vassilis; Abric, Judith; Luton, Dominique; Guibourdenche, Jean; Azria, Elie
Abstract: Objective: To determine if human immunodeficiency virus (HIV) infection or antiretroviral therapy interferes with maternal levels of free human β-chorionic gonadotrophin (hCGβ) and pregnancy-associated plasma protein-A (PAPP-A) and whether any such influence alters first-trimester Down syndrome (DS) screening in HIV-infected women. Study design: We performed a multicenter 1:2 matched case–control study comparing 84 HIV-infected women with singleton pregnancies with controls randomly selected among uninfected women, delivered and screened in the same center and matched for maternal age, geographical origin and fetal sex. Results: Groups did not differ significantly in screening results, although case women showed a slightly lower median free hCGβ multiple of the median (MoM) (1.11 versus 1.24 MoM, p  = 0.32) and higher median PAPP-A MoM (1.45 versus 1.32 MoM, p  = 0.23) than control women. The false-positive rate was similar in the case and control groups (5% versus 6.5%, p  = 0.5). Biomarker levels did not differ when comparing treated and untreated patients with their respective controls, and with one another. Conclusion: First-trimester DS combined screening biomarker levels and calculated risk do not seem to be significantly altered by HIV infection or antiretroviral treatment. This screening strategy appears to be suitable for HIV-infected women.